2010
DOI: 10.1007/s10803-010-1159-8
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Perceptual Load and the Autism Spectrum in Typically Developed Individuals

Abstract: A fundamental task of the cognitive system is to prioritize behaviourally relevant sensory inputs for processing at the expense of irrelevant inputs. In a study of neurotypical participants (n = 179), we utilized a brief flanker interference task while varying the perceptual load of the visual display. Typically, increasing perceptual load (i.e., with greater numbers of search items) reduces interference from a competing peripheral distractor. We show that individuals who score above average on the Autism Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 28 publications
6
35
0
Order By: Relevance
“…This study investigated whether the sensory difficulties experienced by those with ASD (Grandin, 1996;Williams, 1998;Baranek et al, 2006;Leekam et al, 2007) The finding that those with high levels of autistic traits also experience sensory disturbances is consistent with a growing number of studies, which have found differences in visual processing (Grinter et al, 2009a;Grinter, Van Beek, Maybery & Badcock, 2009b;Stewart et al, 2009;Bayliss & Kritikos, 2010;Sutherland & Crewther, 2010) and speech perception (Stewart & Ota, 2008;Yu, 2010) between those with high and low levels of autistic traits. Our results indicate that these differences may be present in multiple sensory domains, and it would be interesting to see whether the differences observed in touch (Cascio et al, 2008) and taste (Tavassoli & Baron-Cohen, 2011) for those with ASD are replicated in low/high AQ scorers within the general population.…”
Section: Discussionmentioning
confidence: 61%
“…This study investigated whether the sensory difficulties experienced by those with ASD (Grandin, 1996;Williams, 1998;Baranek et al, 2006;Leekam et al, 2007) The finding that those with high levels of autistic traits also experience sensory disturbances is consistent with a growing number of studies, which have found differences in visual processing (Grinter et al, 2009a;Grinter, Van Beek, Maybery & Badcock, 2009b;Stewart et al, 2009;Bayliss & Kritikos, 2010;Sutherland & Crewther, 2010) and speech perception (Stewart & Ota, 2008;Yu, 2010) between those with high and low levels of autistic traits. Our results indicate that these differences may be present in multiple sensory domains, and it would be interesting to see whether the differences observed in touch (Cascio et al, 2008) and taste (Tavassoli & Baron-Cohen, 2011) for those with ASD are replicated in low/high AQ scorers within the general population.…”
Section: Discussionmentioning
confidence: 61%
“…A similar finding was also observed in those with high scores on a questionnaire which measures self-reported autistic traits in the general population (Autism Spectrum Quotient, AQ, Baron-Cohen et al, 2001). Specifically, Bayliss & Kritikos, (2011) found that those with above average autism quotient (AQ) scores showed stronger interference from distractors at high levels of load than those with below average AQ scores. Taken together, there is an array of evidence to suggest that individuals with ASD, and also those with high levels of autistic traits, have atypical spatial attention, which may be manifested by reduced suppression of distracting information.…”
Section: Introductionmentioning
confidence: 99%
“…We reasoned that enhanced perceptual capacity as reported in ASC (Remington et al, 2009; and in those without ASC but with high levels of autistic traits (Bayliss & Kritikos, 2011) may enable participants to process relevant and irrelevant items in a simultaneous parallel-like manner. Indeed this has been suggested as one explanation for superior visual search seen in those with ASC (Remington et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Remington et al (2009) demonstrated that individuals with ASD require higher levels of perceptual load to be able to ignore irrelevant distractors, again suggesting enhanced capacity for individuals with ASD. Furthermore, this enhanced capacity seems to be reflected in the severity of autistic traits, as typically developing individuals scoring high on the AQ are affected less by higher perceptual load than individuals scoring low on the AQ (Bayliss and Kritikos 2010). While this concept of enhanced perceptual capacity has been used to explain superior performance in individuals with ASD, it might also explain the results observed in experiment 1 of the present study.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, as the AQ scores in the control population are quite high, this might have lessened the difference between the ASD group and the control group (see e.g. Bayliss and Kritikos 2010). Nevertheless, these considerations do not undermine the finding of superiority in visual search for individuals diagnosed with ASD, as reflected in the 'easy' session.…”
Section: Discussionmentioning
confidence: 99%